The drop down menus are not provided. However, I will help get the solution of the system of equation which is the requirement of the question.
<u><em>Answer:</em></u>
(3,14) and (-2,-1) are the solutions of the system
<u><em>Explanation:</em></u>
<u>The first equation given is:</u>
y = x² + 2x - 1 .........> equation I
<u>The second given equation is:</u>
y - 3x = 5
<u>This can be rewritten as:</u>
y = 3x + 5 ..........> equation II
<u>Equate equations I and II and solve for x as follows:</u>
x² + 2x - 1 = 3x + 5
x² + 2x - 1 - 3x - 5 = 0
x² - x - 6 = 0
(x-3)(x+2) = 0
either x-3 = 0 .........> x = 3
or x+2 = 0 ...........> x = -2
<u>Now, we get the values of y by substituting in equation II as follows:</u>
At x = 3:
y = 3x + 5
y = 3(3) + 5
y = 14
The first solution is (3,14)
At x = -2:
y = 3x + 5
y = 3(-2) + 5
y = -1
The second solution is (-2,-1)
Hope this helps :)
Answer:
- If angle C is 90 degrees (def. of right angle) then the sum of angle A and B has to 90 degrees since angle A + B + C (90°) = 180°
Statements and Reasons:
3. Angle C is 90 degrees because of the definition of right angle.
4. Angle A + angle B + angle C is 180 degrees because of triangle sum.
5. Angle A + angle B + 90 = 180 because of substitution postulate.
6. Angle A + angle B is 90 degrees because of subtraction postulate. (subtract 90 from both sides from the equation above this step).
7. Angle A and angle B are complementary.
Given parameters:
First term of the sequence = x
Second term = x + 2
Third term = x + 4
Sum of the first three terms = 72
Unknown:
First term of the sequence = ?
Solution:
The sum of the first three terms is unknown;
(x) + (x + 2) + (x + 4) = 72
Solve for x;
x + x + 2 + x + 4 = 72
3x + 6 = 72
3x = 72 - 6
3x = 66
x = = 22
The first term of the sequence is 22
Answer:
I think the answer is b^2=8^2-4^2
Step-by-step explanation:
The equation is A^2+B^2=C^2
C^2-A^2=B^2
C^2-B^2=A^2
C is the hypotenuse. You know what a is and all you have to do is show the equation